Unintentional Receptive Ecumenism: From Ecclesial Margins to Ecumenical Exemplar - A New Zealand Case Study - Pratt, Douglas (Review of ecumenical studies, 2016)
The Community Church of St John the Evangelist, situated on a relatively remote island off the east coast of New Zealand, is a unique ecumenical venture supported by the Anglican, Catholic, Methodist and Presbyterian Churches. This paper describes and situates this venture and discusses its development and modus vivendi in light of the paradigm of receptive ecumenism. This paradigm did not feature in the thinking of those who established this ecumenical community church; nevertheless it is argued that the paradigm aptly applies, so yielding the phenomenon of an unintentional receptive ecumenism at work.